Structural and Functional Characteristics of miRNAs in Five Strategic Millet Species and Their Utility in Drought Tolerance - Chakraborty, Animikha; Viswanath, Aswini; Malipatil, Renuka; Rathore, Abhishek; Thirunavukkarasu, Nepolean (Frontiers in Genetics, 2020)
Millets are the strategic food crops in arid and drought-prone ecologies. Millets, by virtue of nature, are very well adapted to drought condition and be able to produce sustainable yield. Millets are bestowed with important nutrients which can help to prevent micro-nutrient malnutrition. Considering adverse effect of climate change and wide-spread malnutrition, millets attained a strategic place to sustain the food and nutritional security. Although, millets can adapt well to the drought ecologies where other cereals completely fail, the yield level is very low under stress. There is a tremendous opportunity to increase the genetic potential of the millet crops in dry lands when the genetics of the drought tolerance mechanism is fully explained. MicroRNAs, are the class of small RNAs, control trait expression since they are part of the gene regulation but hardly studied in millets. Hence, in the present study, novel miRNAs and gene targets were identified from the genomic resources of pearl millet, sorghum, foxtail millet, finger millet and proso millet through in-silico approaches. A total of 1002 miRNAs from 280 families regulating 23158 targets were identified using different filtration criteria in five millet species. The unique as well as conserved structural features and functional characteristics of miRNA across millets were explained. About 84 miRNAs were conserved across millets in different species-combinations which explained the evolutionary relationship of the millets. Further, 215 miRNAs controlling 155 unique major drought-responsive genes, transcription factors and protein families revealed the genetics of drought tolerance that are accumulated in the millet genomes. The miRNAs regulating the drought stress through specific targets or multiple targets showed through a network analysis. The identified genes regulated by miRNA genes could be useful to develop functional markers and used for yield improvement under drought in millets as well as in other crops.